Determination of Cucurbitacin B in Trichosanthes dioica Roxb by HPTLC - Solomon, Joy Ashish; Ganeshpurkar, Aditya; Shrivastava, Nilesh; Bansal, Divya; Dubey, Nazneen (Pharmacognosy Communications)
Background: Trichosanthes dioica Roxb, (Cucurbitaceae), is a perennial herb distributed in Asian subcontinent. The pointed gourd is mainly cultivated as a vegetable. The Charaka Samhita prescribes its use in treating jaundice and alcoholism. Ayurvedic literature depicts its use as a diuretic, cardiotoinc, antiulcer and a laxative. Recent research trend on Trichosanthes dioica Roxb. has also demonstrated its anticancer potential. Objective: The aim of the current work was to develop a new, simple, sensitive, precise, and robust HPTLC method to determine the cucurbitacin content in fruit extracts of Trichosanthes dioica Roxb Linn. Materials and Methods: Trichosanthes dioica Roxb was collected from Jabalpur, India. The dried fruit powder of Trichosanthes dioica Roxb. was extracted with methanol in several batches by Soxhlet extraction, and subjected to HPTLC analysis. The method was also assessed for precision, robustness, limit of detection, limit of quantification, accuracy, ruggedness and specificity. Results: The present HPTLC method was used to establish a cucurbitacin calibration curve in the concentration range of 40 - 240 ng/spot. Regression analysis showed a good linear relationship with r2 > 0.99982. The method followed the criteria of precision, robustness, limit of detection, limit of quantification, accuracy, ruggedness and specificity as per ICH guidelines. Conclusion: Statistical analysis of the data demonstrated that our method was selective and reproducible for estimation of cucurbitacin B.
Keywords: Trichosanthes dioica Roxb.; cucurbitacin B; analytical method development; ICH; HPTLC